Pengaruh Partisipasi Masyarakat dan Akuntabilitas Keuangan Desa Terhadap Persepsi Anggaran Pendapatan dan Belanja Desa - Dharmakarja, I Gede Made Artha; Kusuma, I Gede Komang Chahya Bayu Anta; Putra, Chandra Maulana (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2020)
This study aims to determine the perceptions of rural communities in village financial management in the form of APBDes. How perceptions affect the level of participation of village communities in the preparation of APBDes and accountability for their use. The object of this research is the villagers who are involved and attend the discussion of APBDes management. Primary data in this study is data collected through questionnaires and interviews with respondents. Meanwhile, the secondary data of this research comes from village fund report data. The sampling technique chosen was Stratified Random Sampling, with a total sample of 49 people. This research technique uses multiple linear regression data analysis. The results showed that first, community participation and village financial accountability had a simultaneous effect on the perception of the village income and expenditure budget. Second, community participation does not have a partial that effect on perceptions of village income and expenditure budgets. Third, village financial accountability has a partial effected on perceptions of village income and expenditure budgets